The Factors Determining Open Unemployment in West Java Province: The Role of Wage, Economic Growth, and Education - Nurul Nida Fadhila; Winny Perwithosuci (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The primary objective of this research is to analyze the socio-economic determinants of the open unemployment rate in West Java. The investigation focuses on how regional wage policies, the number of poor people, economic performance, and education levels across different region from 2020 to 2024. Methodology: The analysis based on secondary data from Statistics Indonesia (BPS) and the West Java Open Data Center, estimated using panel data regression. Stata 14 software was used. Model selection was performed using the Chow and Hausman tests, with the Fixed Effect Model identified as the most appropriate specification.Results: Empirical evidence reveals that the number of poor people is positively and significantly related to open unemployment, while economic growth and average length of schooling exhibit a significant negative relationship. Conversely, the minimum wage was not found to have statistically significant effect on open unemployment. Applications/Originality/Value: These findings highlight the importance of strengthening education levels and maintaining economic growth to reduce unemployment in West Java. Meanwhile, the increasing number of poor people actually worsens labor market condition.